The Formation of Fruit Quality in Cucumis sativus L. - Zhang, Juping; Feng, Shengjun; Yuan, Jing; Wang, Chen; Lu, Tao; Wang, Huasen; Yu, Chao (Frontiers in Plant Science, 2021)
Cucumber is one of the most widely grown vegetables in China that provides fresh fruits as an almost indispensable component in the diets of local people. Consequently, fruits of higher quality are more demanded and of higher commercial value. Thus, to breed cucumber varieties of higher fruit quality is one of the main goals for cucumber breeders. In this article, we reviewed the mechanism in the formation of cucumber fruit quality from three aspects: the commercial quality, nutritional quality and flavor quality of cucumber fruit, and summarized the determinants of cucumber fruit quality from the two levels of genetic regulation and cultivation methods, in order to provide perspectives on improving the fruit quality by both cucumber researchers and growers..